Nationalism and the Topos of Threat : A Critical Discourse Analysis of the Argumentation used in the Televised Debates about the Scottish Independence Referendum of Debates about the Scottish Independence Referendum of 2014 - Immonen, Waltteri (fi=Turun yliopisto|en=University of Turku|, 2018)
This thesis examines nationalistic discourse in the televised debates regarding the Scottish independence referendum of 2014. It aims to bridge the gap in research about the different dimensions nationalism has and how they are discursively produced. This thesis also provides a novel theoretical framework for analysing nationalistic discourse. It claims that when discussing about the creation of a new nation-state, there is an inherent element of threat present, which frames the whole discourse. This allows for the identification of a topos of threat that positions the argumentation, and through which the discourse can be reflected, allowing deeper analysis and more fruitful findings. Rather than treating nationalism and discourse as separate entities, this thesis shows how they cannot be separated from one another as nationalism is produced in discourse. This thesis follows Breuilly (1993) in claiming that nationalism is first and foremost political behaviour which seeks to change unwanted circumstances through nationalistic argumentation. Using critical discourse analysis, this thesis found that threat based argumentation was indeed central in the debates. Both campaigns under examination frame their argumentation through the idea of why something is a threat and should thus not be done. For the pro-independence movement the threat was found to be the central government in Westminster and the Conservative party, while the pro-UK campaign insisted that Scotland would be worse off independent. The two debates were found not to be about presenting two competing notions of good but two competing notions of bad. More research is needed to show whether or not this is a general notion in nationalistic argumentation.